Efektivitas penggunaan antibiotik dalam mengobati infeksi bakteri pseudomonas sp pada pasien dengan luka operasi - Justeen, Anabelle Elfrida; Sjahriani, Tessa; Dharmawan, Akhmad Kheru; Syukri, Dwi Marlina (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Surgical Site Infection (SSI) is typically characterized by the discharge of pus, the presence of an inflammatory process, swelling, pain, and a sensation of heat around the wound area. The occurrence of SSI is influenced by various factors, including the type of surgery related to the level of surgical contamination, comorbidities such as age, sex, preoperative body temperature, duration of surgery, and underlying diseases. Purpose: To identify the types of antibiotics used and to evaluate the effectiveness of antibiotic therapy in treating bacterial infections in patients with surgical wounds. Method: This study is a cross-sectional research using a retrospective approach. Results: A total of 80 patients, all of whom were female, were included in this study. With a P-value of 0,004, 28 patients were found to be sensitive to Aminoglycoside antibiotics, while 13 patients were sensitive to Fluroquinolones. Conclusion: There is a fairly strong association between the type of drug and the effectiveness of the administered antibiotic therapy Keywords: Aminoglycosides; Fluroquinolones; Surgical Site Infection (SSI). Pendahuluan: Infeksi Luka Operasi (ILO) ciri biasanya yaitu meliputi keluarnya pus, adanya proses inflamasi, pembengkakan, nyeri, serta sensasi panas pada area luka. Kejadian ILO terpengaruhi oleh berbagai faktor, termasuk jenis operasi yang berkaitan dengan tingkat kontaminasi bedah, komorbiditas seperti usia, jenis kelamin, suhu tubuh pra operasi, durasi operasi, dan penyakit penyerta. Tujuan: Untuk mengetahui jenis antibiotik yang digunakan dan efektivitas penggunaan antibiotik dalam mengobati infeksi bakteri pada pasien dengan luka operasi Metode: Penelitian cross sectional melalui teknik retrospektif. Hasil: Total 80 pasien dengan jenis kelamin keseluruhan yaitu perempuan. Dengan nilai P value 0,004 , pasien yang sensitif terhadap antibiotik Aminoglikosida terdapat 28 pasien sedangkan 13 pasien sensitif terhadap Fluorokuinolon. Simpulan: Terdapat hubungan yang cukup kuat hubungan antara jenis obat dan efektivitas penggunaan antibiotik yang diberikan. Kata Kunci: Aminoglikosida; Fluoroquinolone; Infeksi Luka Operasi (ILO)